Standarisasi Mutu Lulusan sebagai Kesiapan Mahasiswa Calon Guru Profesional pada Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Imron Fauzi; Qurrota A'yun (Journal of Islamic Education Research, 2021)
This article discusses the standardization of graduate quality as the readiness of prospective professional teacher students at the Islamic Religious Education Study Program, Faculty of Education and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University Jember. This study uses a qualitative method by conducting semi-structured interviews, observation, and documentation. Sample selection using the purposive method. The findings of this study are that the standardization of graduate quality consists of 4 components: Student Quality Assistance Books, Curriculum Equivalent Books, Comprehensive Examination Quality Assistance Books, and Internal Quality Assurance Systems. Quality standards for graduates are formulated by the Faculty Quality Assurance Team, along with the Study Program Quality Control Team, as well as lecturers. The implementation of graduate quality standards includes quality bills that must be mastered by students, namely bills for memorizing the letters of juz 30, memorizing tarbawi verses, and memorizing tarbawi traditions. The implementation obstacle encountered was the existence of the SPAN system in the student selection process which was only based on report cards, causing the mapping of the ability to read and write the Koran and religious understanding to be unclear.